A Review of Digital Economy in Business - M. Uma Raman (AG Volumes, 2022)
The economic activity that arises as a result of the billions of daily online connections that are made between individuals, companies, devices, data, and processes is referred to as the digital economy. Hyper-connectivity, which may be defined as the increased interconnectivity of people, organisations, and machines as a consequence of the proliferation of mobile technology, the internet of things (IoT), and the internet as a whole, serves as the foundation of the digital economy. The conceptions of how companies are constituted, how enterprises interact with one another, and how customers receive services, information, and commodities are being challenged as the digital economy begins to take shape and undermine these traditional notions. The global network of economic activity, commercial transactions, and professional relationships that are made possible by information and communications technology (ICT) is referred to as the digital economy. The transition from the third industrial revolution to the fourth industrial revolution is reflected in the rise of the digital economy. The developments that occurred in the latter half of the 20th century as a result of the shift from analogue electrical and mechanical devices to digital technologies are referred to as the third industrial revolution. This revolution is also frequently referred to as the digital revolution. The digital revolution serves as the foundation for the fourth industrial revolution, which is already underway as technologies continue to bridge the gap between the physical and cyber worlds.